An empirical evaluation on quality of insurance services in rural areas of tiruvallur district - Rajasekar, D. (university of Jaffna, 2014)
Service sector has become an important growing industry in many economies in the world. After 1991, service industries play a major role in Indian Economy. Most of the services sector are growing very fast compared to the manufacturing sector .Majority of the Manufacturing units are depending on services. Mobile phone, computers, automobile, durable and non-durable products manufacturing units are depending services like telecommunication, internet, advertising and retailing etc.All service providers need some regulation. Measuring service quality plays a vital role in regulating the service providers. Perception and expectation are important factors to measure quality of services. These two factors are closely related to the behaviour of the customer. Customer behaviour will determine the quality of services but their need, wants and requirements will determine the design, functions of the product and services .Predetermining the customer behaviour and their requirements of both are very difficult to measure.
Keywords: Service sector; computers; automobile